APLIKASI BEBERAPA JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN AWAL RUMPUT GAJAH (Pennisetum purpureum) - Dominggus de Lima; Lily Joris (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2019)
The objective of the research was to determine the effects of different compost application on the early growth of elephant grass (Pennisetum purpureum). The research was conducted at educational field of Animal Husbandry section of Agriculture Faculty Pattimura University. The measurements were number of buds, lesf wide, leaf length and plant height. The research was arranged into Complete Randomized Design with three treatments and five replication. The results showed that there was a highly significant difference on number of buds, leaf length, plant height and leaf wide. It was concluded that the application of 20 tones/ha goat compost produced good effect on early growth of elephant grass (Pennisetum purpureum).